KAJIAN PEMENUHAN KEWAJIBAN PERPAJAKAN WAJIB PAJAK MELALUI E-SYSTEM (STUDI DI KANTOR PELAYANAN PAJAK PRATAMA PEMATANG SIANTAR) - Ehiskia Pardede; Irwan Aribowo (Politeknik Keuangan Negara STAN, 2021)
The e-tax system is an electronic tax system for online counting, depositing, and reporting by taxpayers. This electronic system is implemented to reduce taxpayers time in carrying out their tax obligations. This research was conducted to review the use of e-tax system services in the form of e-registration, e-billing, e-filling, e-form, and e-SPT; find out the obstacles experienced by taxpayers and tax officers in the use of the e-tax system; and find out efforts to optimize the use of e-tax system at KPP Pratama Pematang Siantar. The method was qualitative research. Methods of collecting data were interviews, document collection, and literature study. The result of this research indicate that there is an increase in the use of e-registration and e-billing but there is a decrease in online SPT reporting (e-filling, e-form, and e-SPT); obstacles faced by taxpayers and tax officers both internally and externally; and optimization efforts by increasing tax literacy and encouraging taxpayers tax morale to increase voluntary compliance.